Mainstream and formal epistemology - Hendricks, Vincent F. (Cambridge University Press, 2006)
Mainstream and Formal Epistemology provides the first easily accessible yet erudite and original analysis of the meeting point between mainstream and formal theories of knowledge. Vincent F. Hendricks' book will both define and further the debate between philosophers from two very different sides of the epistemological spectrum.